Consistent decrease in conifer embolism resistance from the stem apex to base resulting from axial trends in tracheid and pit traits - Zambonini, Dario; Savi, Tadeja; Rosner, Sabine; Petit, Giai (Frontiers in Plant Science, 2024)
Drought-induced embolism formation in conifers is associated with several tracheid and pit traits, which vary in parallel from stem apex to base. We tested whether this axial anatomical variability is associated with a progressive variation in embolism vulnerability along the stem from apex to base.We assessed the tracheid hydraulic diameter (Dh), mean pit membrane area (PMA) and the xylem pressure at 50% loss of conductivity (P50) on longitudinal stem segments extracted at different distances from the stem apex (DFA) in a Picea abies and an Abies alba tree.In both trees, Dh and PMA scaled with DFA 0.2 . P50 varied for more than 3 MPa from the treetop to the stem base, according to a scaling of -P50 with DFA -0.2 . The largest Dh, PMA and P50 variation occurred for DFA<1.5 m. PMA and Dh scaled more than isometrically (exponent b=1.2).Pit traits vary proportionally with tracheid lumen diameter.Apex-to-base trends in tracheid and pit traits, along with variations in P50, suggest a strong structure-function relationship that is influenced by DFA. Although the effect of DFA on P50 has not been extensively explored previously, we propose that analyzing the relationship between P50 and DFA could be crucial for a comprehensive assessment of embolism vulnerability at the individual level.